HER2/Neu Expression was Different between Benign, Borderline and Malignant Epithelial Ovarian Tumors - Yona S. Hadisubroto; Ketut Suwiyoga (Indonesian Journal of Obstetrics and Gynecology, 2014)
Objective: To determine the difference of HER2/neu expression in benign, borderline and malignant epithelial ovarian tumor. Method: An analytic cross-sectional study was performed on 49 samples of epithelial ovarian cases which were divided into three groups: twelve cases of benign epithelial ovarian tumor, 9 cases of borderline epithelial ovarian tumor and 28 cases of malignant epithelial ovarian tumor. Paraffin embedded tissue samples was cut, stained with HER2/neu imunohistochemistry and examined in Pathology Laboratory at Sanglah Hospital. The other data was collected from medical record samples. The data was analysed using One Way Anova test and Chi-square test with level of confidence Î± = 0.05. Result: There were 13 cases (46.43%) of the HER2/neu over expression in malignant epithelial ovarian tumors, 2 cases (22.22%) of the HER2/neu over expression in borderline epithelial ovarian tumors and 1 case (9.09%) of the HER2/neu over expression in benign epithelial ovarian tumors. With p = 0.048 (p < 0.05), there are differentiation of HER2/neu expression in benign, borderline and malignant epithelial ovarian tumors. Conclusion: In this study HER2/neu expression was different between benign, borderline and malignant epithelial ovarian tumors. Keywords: benign epithelial ovarian tumor, borderline epithelial ovarian tumor, HER2/neu, malignant epithelial ovarian tumor, ovarian cancer.